Ekološke značajke cestovnih vozila i zakonske mjere - Dušan Jeras (Promet - Traffic&Transportation, 1970)
Increased cares for clean environment and limited sources of energy have inevitably resulted in many laws to be passed. This paper deals with some important aspects of subjects laws treating motor exhaust fuzzes and fuel consumption. The expected effects of these laws as well as possible development trends in designing motor vehicles and their engines have been presented.